Progress in cryptology – INDOCRYPT 2019 : 20th International Conference on Cryptology in India, Hyderabad, India, December 15-18, 2019, Proceedings /: 20th International Conference on Cryptology in India, Hyderabad, India, December 15-18, 2019, Proceedings. (2019) - Unknown
No abstract available